The impact of Sars-Cov-2 infection on the wound healing of cervical treatment in patients with squamous intraepithelial lesions: a retrospective cohort study - Xu, Lili; Wu, Yuying; Li, Chengzhi; Zhao, Renfeng; Wang, Zhibiao (Frontiers in Medicine, 2023)
Objective SARS-CoV-2 infection has been associated with an increase in inflammatory factors, a weakening of the immune system, and a potentially delay in wound healing following surgery or ablative treatment. In this retrospective cohort study, we aimed to investigate the impact of SARS-CoV-2 infection on wound healing following cervical treatment in patients with squamous intraepithelial lesions (SIL). Method From November 2022 to February 2023, patients with SIL who underwent cervical ablative treatment or loop electrosurgical excision procedure at the People’s Hospital of Guangxi Zhuang Autonomous Region, China, were enrolled in the study. Of these, 29 patients who developed symptoms of SARS-CoV-2 infection and confirmed by an antigen test within one month after cervical treatment were included as experimental group, while the other 31 patients who received cervical treatment after recovering from SARS-CoV-2 infection were included in the control group. The cervical wound condition of all patients was documented using colposcopy immediately and one month after the procedure. Image J software was utilized to analyze the wound healing rate at one month post-treatment, and the wound healing status between two groups was compared. A vaginal discharge examination was performed before and one month after cervical treatment. Results No significant differences in age, severity, treatment, or time between groups. Experimental group had significantly lower healing rate 83.77(62.04, 97.09) % than control 98.64(97.10, 99.46)%，p < 0.001, and a higher scab non-shedding rate (24.14% vs. 3.22%, p = 0.024). Among patients who were infected with SARS-CoV-2 after undergoing cervical treatment, we observed 5 out of 7 patients (71.43%) contracted SARS-CoV-2 within 2 weeks after cervical treatment. No significant correlation was found between white blood cell count or leukocyte esterase in vaginal discharge and delayed wound healing of the cervix (p = 0.947 and 0.970, respectively). Conclusion SARS-CoV-2 infection may prolong the healing time of cervical treatment in patients with SIL. To minimize the risk of delayed healing, it’s crucial for patients to avoid viral infections such as SARS-CoV-2 within the first month of treatment. Taking necessary precautions to prevent infection is essential for successful cervical treatment outcomes in patients with SIL.